2012
DOI: 10.1515/znc-2012-1-206
|View full text |Cite
|
Sign up to set email alerts
|

The Saponin-Rich Fraction of a Gymnema sylvestre R. Br. Aqueous Leaf Extract Reduces Cafeteria and High-Fat Diet-Induced Obesity

Abstract: We examined the antiobesity effect of a saponin-rich fraction of a Gymnema sylvestre R. Br. aqueous leaf extract (SGE) using cafeteria and high-fat diet-induced obese rats for a period of eight weeks. SGE was orally administered at a dose of 100 mg/kg body weight once a day to the treatment group. It signifi cantly decreased the body weight, food consumption, visceral organs weight, and the levels of triglycerides, total cholesterol, low-density lipoproteins, very low-density lipoproteins, atherogenic index, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In the human body, saponins can bind to bile salts to reduce cholesterol absorption (Marrelli et al, 2016). Moreover, in rats, it was shown that a saponin-rich diet resulted in the reduction of body weight, total cholesterol, triglycerides, very-low-density lipoproteins (VLDL), and low-density lipoproteins (LDL) in serum (Latha et al, 2011;Reddy et al, 2012). Alfalfa saponin extract (ASE) was found to have cholesterol-lowering effects (Wang et al, 2011;Marrelli et al, 2016).…”
Section: Saponinsmentioning
confidence: 99%
“…In the human body, saponins can bind to bile salts to reduce cholesterol absorption (Marrelli et al, 2016). Moreover, in rats, it was shown that a saponin-rich diet resulted in the reduction of body weight, total cholesterol, triglycerides, very-low-density lipoproteins (VLDL), and low-density lipoproteins (LDL) in serum (Latha et al, 2011;Reddy et al, 2012). Alfalfa saponin extract (ASE) was found to have cholesterol-lowering effects (Wang et al, 2011;Marrelli et al, 2016).…”
Section: Saponinsmentioning
confidence: 99%
“…Obesity is a predisposing factor to many serious lifestyle diseases such as CVD, diabetes, hypertension, and so on. GS has shown potent anti‐obesity properties, such as reducing plasma lipids and decreasing body weight and BMI (Luo, Kashiwagi, Shibahara, & Yamada, 2007; Reddy, Latha, Vijaya, & Rao, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…GS has been widely used in folk medicine as a treatment for diabetes and other disorders (Grover et al, 2002;Porchezhian and Dobriyal, 2003;Bradley et al, 2007;Kanetkar et al, 2007;Leach, 2007;Reddy et al, 2012), and there is an extensive scientific literature suggesting that GS extracts contain biologically active compounds that exert anti-diabetic effects (Sinsheimer et al, 1970;Yoshikawa et al, 1997aYoshikawa et al, , 1997bSugihara et al, 2000;Ye et al, 2000;Zhu et al, 2008;Kang et al, 2012). We have previously reported that OSA W , a novel high molecular weight GS extract, has direct insulinotropic activities on b-cell lines (Liu et al, 2009) and isolated human islets in vitro (Liu et al, 2009;Al-Romaiyan et al, 2010b), and has beneficial effects on glycemic control in patients with T2DM (Al-Romaiyan et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%